The chemical properties of the soil in various degraded land classes: A case study of the Prafi Watershed, West Papua - Kubangun, Siti Hadjar; Baja , Sumbangan; Zubair, Hazairin; Arif , Samsu (Journal of Degraded and Mining Lands Management, 2026)
Land degradation has become a global environmental issue due to its impact on soil quality and the sustainability of terrestrial ecosystems. However, empirical evidence on soil quality, particularly the chemical properties of degraded soils in the Prafi Watershed, is still limited. This study aimed to analyze the chemical properties of soil in five land classes designated in the national critical land map. A total of 20 composite soil samples were collected from locations representing each degradation class and analyzed for soil chemical properties, including soil organic carbon (SOC), total nitrogen (TN), available P, soil pH, exchangeable base cations, cation exchange capacity (CEC), and base saturation (BS). Thresholds for each parameter were set based on the soil analysis, and statistical differences among classes were analyzed using one-way ANOVA followed by Tukey HSD. Base saturation, calcium, magnesium, potassium, SOC, and TN significantly differed between undegraded land and the four classes of degraded land, in which leaching and soil disturbance caused losses of organic matter and base cations. Other parameters, including Na, available P, pH, and CEC, were not significantly correlated with the degree of degradation. This is because these parameters are controlled by internal soil reactions and parent material at the study site. These results verify the key role of SOC dynamics and BS status induced by environmental effects in degraded land. Rehabilitation of degraded land can be achieved through reforestation, agroforestry, and the application of organic matter. Additional investigations should be conducted with more equitable sample sizes per land use type to discern the effects of land management.